Digital-twin-based improvements to diagnosis, prognosis, strategy assessment, and discrepancy checking in a nearly autonomous management and control system. (February 2022) - Lin, Linyu; Athe, Paridhi; Rouxelin, Pascal; Avramova, Maria; Gupta, Abhinav; Youngblood, Robert; Lane, Jeffrey; Dinh, Nam
Highlights: The development and assessment of digital twins of different functions. The development and assessment of a NAMAC system. The demonstration of NAMAC and discrepancy checker on a EBR-II simulator. Abstract: The Nearly Autonomous Management and Control System (NAMAC) is a comprehensive control system that assists plant operations by furnishing control recommendations to operators in a broad class of situations. This study refines a NAMAC system for making reasonable recommendations during complex loss-of-flow scenarios with a validated Experimental Breeder Reactor II simulator, digital twins improved by machine-learning algorithms, a multi-attribute decision-making scheme, and a discrepancy checker for identifying unexpected recommendation effects. We assess the performance of each NAMAC component, while we demonstrate and evaluated the capability of NAMAC in a class of loss-of-flow scenarios.